THE MAKING OF STRATEGY; RULERS, STATES AND WAR - Francois Vreÿ; Abel Esterhuyse (Scientia Militaria, 2012)
The Making of Modern Strategy in the product of a spectrum of contributors working on the concept of strategy and in particular the strategy formulation processes. These contributors include not only historians but also political scientists, some of whom focus on security and strategic studies. Thus editors and contributors represent a necessary balance, as the making of strategy requires insights and understanding of both fields. Throughout the book the writers focus upon the historical Selous Scouts and the Fireforce Commandos of the Rhodesian Light Infantry are all here. Viewers are treated to an expose of their training regimes, weaponry and bush tactics. A point of note here is what Lt Col Ron Reid-Daly refers to as "that baboon" in his book - Selous Scout; Top Secret War. Well that baboon, or another one surprisingly similar, is a star attraction in the Pamwe Chete portion of this video - I found it revolting but aspiring bush battlers would probably disagree!